Journey - Becker, Aaron, 1974- (Somerville, Massachusetts : Candlewick Press, 2013)
Using a red marker, a young girl draws a door on her bedroom wall and through it enters another world where she experiences many adventures, including being captured by an evil emperor.
A wordless picture book.
Keywords: Doors -- Juvenile fiction; Drawing -- Juvenile fiction; Magic -- Juvenile fiction; Stories without words; Picture books for children; Doors -- Fiction; Drawing -- Fiction; Magic -- Fiction; Fantasy; Stories without words